2017
DOI: 10.1007/s11999-017-5302-0
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Prophylaxis for Total Joint Arthroplasty: Incorrectly Dosed and Has a Higher Rate of Periprosthetic Infection Than Cefazolin

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 31 publications
1
62
1
1
Order By: Relevance
“…As the number of TJAs increases, the rate of complications may rise. Infections after TJA despite antibiotic prophylaxis occur in approximately 1% to 2% of cases . Beside infections, other implant‐related complications such as malalignment, loosening, skin changes, pain and swelling may occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the number of TJAs increases, the rate of complications may rise. Infections after TJA despite antibiotic prophylaxis occur in approximately 1% to 2% of cases . Beside infections, other implant‐related complications such as malalignment, loosening, skin changes, pain and swelling may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Infections after TJA despite antibiotic prophylaxis occur in approximately 1% to 2% of cases. 5 Beside infections, other implant-related complications such as malalignment, loosening, skin changes, pain and swelling may occur. One potential cause that has been widely discussed is a hypersensitivity reaction to a metal or bone cement component.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal antibiotic selection and dosages specifically for TJA, however, remain controversial. For instance, a recent large database study noted a 32% higher risk of PJI when noncephalosporin antibiotics such as vancomycin were used for preoperative prophylaxis 7,47,48 . This may be due to issues such as weight‐based underdosage or improper administration protocols 48 .…”
Section: New Advancements In Prevention Of Pjimentioning
confidence: 99%
“…The brief and erratic nature by which bone cement elutes antibiotics into the articular space further impairs their antimicrobial effectiveness [28]. Furthermore, in addition to resistance against antibiotics within bone cement, recent serological studies of patients undergoing TJA have shown that when intravenous vancomycin is given before surgery to prophylactically prevent PJI, the dose given is either insufficient to achieve proper bacteriostatic concentrations [29], or is high enough to cause acute kidney injury [30]. Therefore, significant efforts are needed both to improve the use of antibiotics within bone cement and systemically to prevent the onset of PJI.…”
Section: The Pathophysiology Of Pji: the Periprosthetic Environment Amentioning
confidence: 99%